The association between sleep duration and excess body weight of the American adult population: a cross-sectional study of the national health and nutrition examination survey 2015-2016 - Qing Li (BMC, 2021)
Abstract Background We intend to explore whether sleep duration is associated with overweight and obesity among the adult American population. Furthermore, we stratified the study population by age and sex in the subgroup analysis to investigate the potential disparities between adults and older adults, and men and women. Methods In total, 2459 individuals from the 2015-2016 National Health and Nutrition Examination Survey cycle were included for analysis in this study. Sleep duration was assessed by the Sleep Disorders Questionnaire. Classification of the short-sleep, normal-sleep, and long-sleep group was based on the recommendation of the National Sleep Foundation. Bodyweight was measured during the physical examination. Multivariate logistic regression models were implemented. Results We observed a significantly higher overweight incidence in the short-sleep group compared to the normal-sleep group (OR = 1.825, 95%CI: 1.251-2.661, P = 0.004). Short-sleep (OR = 1.832, 95%CI: 1.215-2.762, P = 0.007) duration and long-sleep duration (OR = 1.370, 95%CI: 1.043-1.800, P = 0.027) were associated with higher prevalence of obesity. When stratified by age, short-sleep also increased the overweight and obese incidence 1.951 and 1.475 times in the adult group. In the sex-stratified subgroup analysis, the short-sleep group showed 2.49 times higher overweight incidence among females. The prevalence of obesity was 2.59 times higher in the short-sleep group and 1.698 times higher in the long-sleep group in the female population. Conclusions Sleep duration is associated with the occurrence of overweight and obesity, with sleep duration less than 7 h increase the overweight and obesity rate nearly 2 folds comparing to sleep 7-9 h.